(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
An experiment was conducted at the Soil Science Field Laboratory of Bangladesh Agricultural University, Mymensingh during aman season of 2015 to evaluate the effect of deep placement of N fertilizers on nitrogen use efficiency and yield of BRRI dhan46 under flooded condition. The soil was silt loam in texture having pH 6.27, organic matter content 1.95%, total N 0.14%, available P 3.16 ppm, exchangeable K 0.09 me% and available S 10.5 ppm. The experiment was laid out in a randomized complete block design with three replications. There were eight treatment combinations including T1 (Control), T2 (PU, 104kgN/ha), T3 (USG, 104kgN/ha), T4 (USG, 78kg N/ha), T5 (USG, 52kg N/ha), T6 (NPK briquette, 104kgN/ha) and T7 (NPK briquette, 78kg N/ha) and T8 (NPK briquette, 52kg N/ha). All the treatments except T6, T7 and T8 received 20 kg P and 50 kg K/ha as TSP and MoP, respectively. Treatments T6, T7, T8 received NPK briquettes fertilizer. Prilled urea was applied in three equal splits. USG and NPK briquettes were applied at 10 DAT and the briquettes were placed at 8-10 cm depth in the center of four hills in alternate rows. The yield attributes, and grain and straw yields of BRRI dhan46 responded significantly to the application of PU, USG and NPK briquettes under flooded condition. The highest yields of grain (5828 kg/ha) and straw (6116 kg/ha) were recorded in T3 and the lowest values of grain and straw yields (3522 and 3783 kg/ha, respectively) were found in the control. Deep placement of N fertilizers also enhanced the N use efficiency, N uptake and apparent recovery by BRRI dhan46. The maximum N use efficiency (22.17 kg grain increase per kg N applied) was found in T3 and the minimum value (9.31 kg grain increase per kg N applied) was recorded in T8. The results reveal that the deep placement of USG (104 kg N/ha) accelerated the N uptake, N recovery and N use efficiency by BRRI dhan46 as compared to other treatments. Therefore, application of 104 kg N/ha as USG may be recommended for profitable cultivation of aman rice, BRRI dhan46. Asian Australas. J. Biosci. Biotechnol. 2017, 2 (3), 219-225